The Fathers in Family Life - Lewis, Charlie (2012)
This article discusses the father's perspective on family life. In spite of a consensus among researchers fromdifferent disciplines about the importance and influence of the father in child development, and that nearly for 30 years, theyhave been studying his role, the results are yet inconclusive. The main objective of this paper is to stimulate Brazilian researchersto study the role of the father in child development, especially within the family context, providing an overview of what isknown currently about fathers in developmental psychology as well as giving some suggestions about the future trends infather research. So, it discusses the following aspects: dimensions and factors which influence the paternal involvement,especially within the family; fatherhood and family systems in transition; paternal influences on children; and, finally, why isimportant to continue studying the father role.